2019
DOI: 10.3390/cells8070746
|View full text |Cite
|
Sign up to set email alerts
|

Roscovitine Attenuates Microglia Activation and Monocyte Infiltration via p38 MAPK Inhibition in the Rat Frontoparietal Cortex Following Status Epilepticus

Abstract: Under physiological conditions, microglia are unique immune cells resident in the brain that is isolated from the systemic immune system by brain-blood barrier. Following status epilepticus (SE, a prolonged seizure activity), microglia are rapidly activated and blood-derived monocytes that infiltrate the brain; therefore, the regulations of microglia activation and monocyte infiltration are one of the primary therapeutic strategies for inhibition of undesirable consequences from SE. Roscovitine, a potent (but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 45 publications
4
36
1
Order By: Relevance
“…5C). Our results were consistent with previous studies [36][37][38] that p38 MAPK signaling was vital in activated microglia to release inflammatory cytokines, these findings also indirectly confirmed our hypothesis that activated microglial may lead to the apoptosis of photoreceptor by releasing inflammatory cytokines, which provides a plausible explanation about the mechanism between Aβ 1−42 induced microglia and photoreceptor apoptosis in AMD (Fig. 6).…”
Section: Discussionsupporting
confidence: 93%
“…5C). Our results were consistent with previous studies [36][37][38] that p38 MAPK signaling was vital in activated microglia to release inflammatory cytokines, these findings also indirectly confirmed our hypothesis that activated microglial may lead to the apoptosis of photoreceptor by releasing inflammatory cytokines, which provides a plausible explanation about the mechanism between Aβ 1−42 induced microglia and photoreceptor apoptosis in AMD (Fig. 6).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, with BIRB 796, the inhibitor of p38 MAPK phosphorylation, we found that the mRNA levels of in ammatory cytokines, including IL-1β, COX-2, TNF-a and iNOS, were decreased signi cantly under the treatment of BIRB 796 in microglia ( Figure 5C). Our results were consistent with previous studies [36][37][38] that p38 MAPK signaling was vital in activated microglia to release in ammatory cytokines, these ndings also indirectly con rmed our hypothesis that activated microglial may lead to the apoptosis of photoreceptor by releasing in ammatory cytokines, which provides a plausible explanation about the mechanism between Aβ 1-42 induced microglia and photoreceptor apoptosis in AMD ( Figure 6).…”
Section: Discussionsupporting
confidence: 93%
“…Alzet 1007D osmotic pump contained (1) vehicle, (2) SB202190 (0.3 mg/mL), (3) wortmannin (0.1 nmol), (4) 3CAI (25 μM), and (5) U0126 (25 μM). In our previous studies [14,[16][17][18]30,31], each treatment did not show behavioral and neurological defects and could not change the seizure susceptibility and seizure severity in response to pilocarpine. Three days after surgery, this group was induced with SE by lithium chloride (LiCl)-pilocarpine.…”
Section: Surgerymentioning
confidence: 83%
“…Serum extravasation was measured, as previously described [14,17,18,31]. Aforementioned, sections were incubated in biotinylated rat IgG and ABC complex (Vector, #PK-6100, Burlingame, CA, USA, diluted 1:200).…”
Section: Measurements Of Serum Extravasation and The Volume Of Gfap-dmentioning
confidence: 99%